EFFECT OF MIXING THE CALF FECES WITH COASTAL SANDYSOIL ON THE GROWTH OF CORN PLANT (Zea mays) - Agung Prabowo; Soemitro Padmowijoto; Zaenal Bachruddin; Abdul Syukur (Pusbindiklat - LIPI, 2011)
This research was intended to determine the effect of combination calf feces and coastal sandy-land on the growth of corn plant. This experiment was arranged in a 2x3x2 factorial pattern of completely randomized design. First factor was calf feces of with and without microbe treatment, second factor was three levels of feces incubation which were 0 day (I-0), 20 days (I-20), and 40 days (I-40), and third factor was fecal dosages of 15 ton/ha (D15) and 30 ton/ha (D30). Parameters of plant height, dry, and wet weight of roots and vegetative, chemical and physical properties of mixture of calf feces and coastal sandy-land were observed. The plant height was observed weekly. There was a signiﬁ cant difference (P<0.05) on combination of feces without and with microbe treatment,fecal incubation time and dosage on the plant height. There was a tendency of increasing fecal dosage and fecal incubation time on the increase of plant height. This study suggests that calf feces could improve the corn plant growth in coastal sandy-land.